Youth and crime: a study of rural hybrids in Ogun State (1998)
Urban bias strategy as the development policy in developing nations has contributed largely to the problem of rural-urban migrations in these nations. Attention has therefore been focussed, mainly, on the effect of migration to the rural and urban areas. Toa large extent, however, it is becoming increasingly difficult for youths - educated in European style with the hope of securing European-style job opportunities - to migrate to the urban areas due to the growing economic crisis and depression since the 1980s - with its effect significantly in urban areas. Consequently, this has led to the emergence of a group of youths we refer to as 'rural hybrids'. This study sets out to inquire into the emergence of this group; investigate their life-style; and ascertain their impact on the rural areas. Using the dis-articulation theory, we examined the emergence of this group. We found out that this group engages in activities considered to be criminal and their way of life is totally contradictory to what the typical rural-dwellers expect. As such, they are likely to contribute negatively to the orientation-of the younger generation corning after them. On the whole, therefore the rural areas are likely to be significantly affected in the future particularly in the areas of crime and violence.